Oestrogen receptors and survival in early breast cancer. Issue 6302 (14th November 1981) - Croton, R; Cooke, T; Holt, S; George, W D; Nicolson, R; Griffiths, K
Abstract : Oestrogen receptor status was related to survival in 414 patients with primary breast cancer. Women with oestrogen receptors in their tumours survived significantly longer than those without receptors; this was true for both premenopausal and postmenopausal women and also when the patients were subdivided into those with and without axillary metastases. Patients with axillary metastases and no oestrogen receptors in their tumours had the worst prognosis, while women with axillary metastases and oestrogen receptors had a death rate similar to that of women with no axillary metastases and no receptors. Patients without oestrogen receptors and with no axillary metastases were identified as a high-risk group, and it would seem appropriate to include such patients in future trials for adjuvant therapy in early breast cancer.